Surgical Management of Extensor Digitorum Brevis Manus Anomaly with a Dorsal Ganglion Cyst - Geraghty, Feargal J.; Anderson, Lisa; Mir, Haaris; Daniali, Lily; Imbriglia, Joseph E.; Pulikkottil, Benson J. (Journal of Wrist Surgery, 2021)
Background The most common soft tissue tumor of the hand is the dorsal ganglion cyst and often is an indication for surgical excision. The differential diagnoses for dorsal hand masses include but are not limited to tenosynovitis, epidermoid cyst, abscess, lipoma, xanthoma, rheumatoid nodule, tophus, carpal boss, myositis ossificans, foreign body granuloma, neoplasm, and anomalous muscles.Case Description Our case report reflects the latter, a 33-year-old female who presented with a 3-year history of a symptomatic dorsal ganglion cyst of her left wrist. She is a female in her 30s, with progressive, worsening pain on wrist extension. Intraoperatively, it was determined that an anomalous extensor digitorum brevis manus (EDBM) was present and may have contributed to her pain and was excised.Literature Review The literature is sparse with the surgical management of EDBM. This case study aims to explore algorithms for managing simultaneous EDBM with a dorsal wrist ganglion, which is clinically relevant for any hand surgeon, when faced with a similar intra-operative management situation.
Keywords: extensor; digitorum; brevis; manus; anomaly